An Educational Digital Game Driven Strategy to Support the Teaching-Learning of Algorithms and Motivate Female Information Systems Students - Yamashita, Victoria Tiemi; Nunes, Eduarda; Lauschner, Luana; Campos, Luciana; GonçAlves, Luciana Brugiolo; Valle, Pedro Henrique Dias; Quintela, Bárbara De Melo; Oliveira, Alessandreia Marta De (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Research has highlighted the various benefits to a project or product when gender diversity is present in information technology teams, yet women are underrepresented in the area. Problem: Although women constitute the majority of students enrolled in undergraduate courses, there is a noticeable gender disparity in technology. Solution: Acquiring proficiency in fundamental subjects, such as algorithms, can motivate women entering the Information Systems course to persevere and overcome barriers. Games, as an important ally in the teaching-learning process, can help in this context. Is Theory: This work was conceived under the aegis of cyberfeminism, which defends the use by women of new information and communication technologies for empowerment and increasing female representation. Method A questionnaire was administered to female students to identify relevant characteristics for defining a digital game. After that, a digital game was designed by female students based on the responses and focusing on their reality at the beginning of the course at the university. A heuristic and feedback evaluation were carried out to evaluate the first version of the developed game. Summary of Results: According to the evaluations presented in this work, the content covered is relevant to the game’s theme, and the examples help apply the concepts of Algorithms in a motivating way for female students in the Information Systems course. Contributions and Impact in the IS area: A game developed by women with relatable characters can encourage the entry and permanence of women in Information Systems courses and related areas.